Revised Ordinances of the City of Fort Worth, Texas, 1873-1884, at 207, Ordinance no. 157, § 1 (1885) - (:unkn) unknown (My University, 1885)
Any person carrying concealed on or about his person any pistol, dirk, dagger, slung shot, sword cane, spear, brass knuckles, Bowie knife, or any other kind of knife manufactured or sold for the purpose of offense or defense, unless having or carrying the same on or about his person for the lawful defense of the State as a militiaman, in actual service, or as a peace officer or policeman, shall be guilty of a misdemeanor, and on conviction thereof, shall be punished by fine of not less than twenty-five nor more than one hundred dollars.
Keywords: CARRY - CONCEALED